Retention of Large Biological Molecules by Size-Exclusion Chromatography. (13th April 2017) - Lee, Yu Ri; Li, Xiaoxia; Ma, Wanwan; Row, Kyung Ho
ABSTRACT: Size-exclusion chromatography has been developed for the separation of large biological molecules including proteins, polymers, peptides, nucleic acids, and polysaccharide according to their molecular size. This study determined the retention factors for dextran (5, 25, 50, 270, 670, and 1100 kDa) and polysaccharides, such as fucoidan, alginic acid, and laminarin, in the size-exclusion chromatography stationary phase. In addition, the molecular weights and retention factor of three polysaccharides were calculated from the dextran standard curve. The largest retention factor was 4.26 using the size-exclusion chromatography columns (5 kDa dextran). The molecular weights of fucoidan, alginic acid, and laminarin were determined to be 250, 200, and 5 to 64 kDa, respectively.